Formulasi Self-Nanoemulsifiying Drug Delivery System (SNEDDS) Asam Mefenamat menggunakan VCO dengan Kombinasi Surfaktan Tween dan Span - Muhamad Handoyo Sahumena; Suryani Suryani; Neni Rahmadani (State University of Gorontalo, 2019)
Mefenamic acid is a non-steroidal anti-inflammatory drug (NSAID) which has analgesic, anti-inflammatory and antipyretic effects. Mefenamic acid works by inhibiting prostaglandin synthesis as an inflammatory mediator. Mefenamic acid has low drug solubility and a long process of dissolution in the body which greatly affects the speed of absorption and bioavailability of the drug. In this study, mefenamic acid nanoemulsion formulation was carried out through a Self-Nanoemulsifying Drug Delivery System (SNEDDS) delivery system. SNEDDS is a drug delivery method through isotropic oil extraction, surfactants, cosurfactans and drug that form oil in water (m/a) emulsions which when in contact with the water phase in the digestive tract wiil from a nanoemulsion that occurs spontaneously so that the drug dissolves with a particle size small so as to increase the effective surface area for absorption. The purpose of the study was to determine the ratio of surfactant and cosurfactant composition to the optimum formula of SNEDDS of mefenamic acid with VCO as an oil phase. The SNEDDS formula was obtained by mixing the surfactants tween 80 and span 80, cosurfactant PEG 400 and VCO as the oil phase using the characterization of determining the optimum formula, namely emulsion formation, transmittance and emulsification time. The composition of the optimum formula of SNEDDS of mefenamic acid is 1 mL VCO; 1 mL PEG 400; 6 mL tween 80; 1 mL span 80. Optimum formula showed clear emulsion results, with transmittance values of 89,04% and emulsification time under 1 minute. In this study produced the optimum formula SNEDDS the met the criteria based on droplet size parameters of 153,5 nm, potential zeta value of 8,2 mV and showed good stability.